Od socjaldemokracji do nacjonalizmu: zmiany w ideologii i światopoglądzie Dmytra Doncowa - Procik, Ìrina (L'vìvs'kij nacìnal'nij unìversitet ìmenì Ìvana Franka, 2019)
Dmytro Dontsov is one of the most controversial figures in Ukrainian political and legal opinion of the 1st half of the ХХ th century, a man whose political views have undergone drastic changes having evolved from sympathizing with the left wing to propagandizing ideas of the right wing.In the article on the basis of analysis of the three Dmytro Dontsov’s conceptual works «Modern political situation of the nation and our tasks» 1913, «The basis for our politics» 1921 and «Nationalism» 1926 the evolution of the author’s ideological beliefs has been traced; the author who has abandoned social democracy and through conservatism has come to valid or, in other words, active nationalism as the only ideological salvation of the non-state for the time being Ukrainian nation.Dmytro Dontsov’s evolution of ideas is based on being aware of inevitability of Ukrainian and Russian opposition, civilizational and cultural conflict with Russia and also understanding it as the central competition not only in the central-eastern, but also in the whole Europe. Analysis of Dmytro Dontsov’s works gives us the reason to talk about the appearance of the right – conservative and і nationalistic – movement in Ukraine, ideology of which was based on the heroic past of Ukraine, religious thinking, idealism and irrationalism; its final goal was to renew traditions of Ukrainian nation as a political nation.Perspective of this research consists in the fact that detailed studies of the very spreading political journalism of the ideologist of Ukrainian nationalism will make it possible to understand peculiarities of nationalism in Ukraine, and also in the whole central-eastern Europe.
Keywords: Doncow, Dmytro (1883-1973); ideolog ukraińskiego nacjonalizmu; czynny aktywny nacjonalizm; ukraiński nacjonalizm; socjaldemokracja; naród polityczny